Supervisi Pembelajaran Sebagai Upaya Mewujudkan Keefektifan Manajemen Kelas - Nunuk Hariyati; Sri Setyowati; Amrozi Khamidi; Vicka Bella Fahira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effectiveness of learning supervision in achieving classroom management at the school. The research subjects include a primary school and a kindergarten in Surabaya. The method used in this study is qualitative descriptive with a case study approach. The results indicate a positive correlation between the structured and systematic supervision process, as outlined by Glickman, and the progress in classroom management carried out by teachers. This approach also has a positive impact on student learning outcomes.